Supercritical water gasification of black liquor with wheat straw as the supplementary energy resource. (14th June 2019) - Cao, Changqing; Zhang, Yi; Li, Linhu; Wei, Wenwen; Wang, Gaoyun; Bian, Ce
Abstract: Supercritical water gasification (SCWG) is a new treatment of black liquor (BL) for both energy recovery and pollution management. To provide more energy for the pulp mill, it is proposed to use the pulping raw material as supplementary energy source because it is readily available, inexpensive and renewable. In this study, co-gasification of BL and wheat straw (WS) in supercritical water was investigated. The synergistic effect was observed in the co-gasification because the addition of wheat straw can make better use of the alkali in BL. The maximum improvement of the gasification by the synergistic effect was obtained with the mixing ratio of 1:1. The influences of the temperature (500–750 °C), reaction time (5–40 min), mixture concentration (5.0–19.1 wt%), mixing ratio (0–100%) and the wheat straw particle diameter (74–150 μm) were studied. It was found that the increase of temperature and reaction time, and the decrease of concentration and wheat straw particle size favored the gasification by improving the hydrogen production and gasification efficiency. The highest carbon gasification efficiency of 97.87% was obtained at 750 °C. Meanwhile, the H2 yield increased from 12.29  mol/kg at 500 °C to 46.02  mol/kg. This study can help to develop a distributed energy system based on SCWG of BL and raw biomass to supply energy for the pulp mill and surrounding communities. Graphical abstract: Image 1 Highlights: Raw biomass was gasified with black liquor to improve the energy supply for pulp mill. Synergistic effect of wheat straw and black liquor was observed in their co-gasification. Maximum carbon gasification efficiency of 97.87% was achieved in co-gasification.